Realizatsiia didakticheskikh vozmozhnostei IKT pri obuchenii shkol'nomu kursu matematiki - Safonov V. I. (Actual problems of education fundamentalization)
the maintenance of a school course of mathematics is presented in article and shown how didactic opportunities of ICT at its studying can be realized
Keywords: обучение; математика; training; дидактические возможности ИКТ; mathematics; didactic opportunities of ICT